Analysis of the inverse Born series: an approach through geometric function theory. (1st July 2022) - Hoskins, Jeremy G; Schotland, John C
Abstract: We analyze the convergence and approximation error of the inverse Born series, obtaining results that hold under qualitatively weaker conditions than previously known. Our approach makes use of tools from geometric function theory in Banach spaces. An application to the inverse scattering problem with diffuse waves is described.